PENGEMBANGAN MODEL BRAIN-BASED LEARNING (BBL) BERBASIS GAMIFIKASI PADA PEMBELAJARAN DARING BIOLOGI SMA DAERAH PERTANIAN INDUSTRIAL - Aulia Fitria Damayanti; Jekti Prihatin; Pujiastuti Pujiastuti (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2021)
Implementation of online learning during the Covid-19 pandemic is not well structured, so the teacher must be able to innovate fun learning and students active learning in process to optimize potential of the environment industrial agricultural. This can applying Brain-Based Learning (BBL) model combined with gamification approach. The study to produce a valid, practical, and effective BBL-Gamification model biology online learning to increase outcomes learning and critical thinking skills in industrial agricultural areas. The development procedure used ADDIE development model which in five stages Analysis, Design, Development, Implementation, and Evaluation. The result of product validation guidebooks models, learning syllabus, lesson plans, LKPD as well pre test and post test questions is 89,96 (very valid). The practicality of learning model obtained the practice sheet learning of students and teacher responses. The average practicality of student responses is 87,73 (very good) and the teacher responses is 90 (very good).